Pilomatrixoma in the cheek: a clinical case report - Mario Vitor Carcassola,; Wladimir Gushiken de Campos,; Celso Augusto Lemos,; Basilio de Almeida Milani,; Ricardo Luiz Psciolaro,; Marcelo Minharro Ceccheti, (Autopsy and Case Reports, 2022)
Pilomatrixoma is a follicular benign tumor of unknown etiology that originates in the matrix of a hair follicle. It develops more frequently in children and young adults, with a slight predominance in female patients. It is a slow-growing tumor that presents as a mobile nodule, firm, and with well-defined borders. The present study aimed to report the clinical, histopathologic, and radiographic aspects of pilomatrixoma in the cheek area of a 20-year-old female patient as the established treatment at an oral maxillofacial department. Pilomatrixoma is rarely included in the differential diagnosis of masses and nodules in the skin, and it is often confused with other nodular lesions, such as epidermoid cysts. The diagnostic method to identify this entity is an incisional biopsy. Because of its high incidence in the head and neck region, oral surgeons should be well-acquainted with this type of tumor so that it can be included as a diagnostic hypothesis of masses and nodules of the head and neck.